A narrative review of the pathophysiology of sepsis in sub-Saharan Africa: Exploring the potential for corticosteroid therapy - Phoebe Gruccio; William S. Girard; Amelia D. Badipour; Reagan Kakande; Victor Adejayan; Muhammad Zulfiqar; Michael Ndyomugabe; Philemon Ojuman; Philemon Ojuman; Megan Nul; Jeffrey Sturek; ,Tania Thomas; et al. (PLOS Glob Public Health, 2025)
Sepsis remains a significant global health threat with a disproportionate burden in low-income countries including those in sub-Saharan Africa where case fatality rates are as high as 30% to 50%. Defined as a severe systemic response to infection, sepsis leads to widespread immune dysregulation and organ dysfunction, including adrenal insufficiency. Critical illness-related corticosteroid insufficiency (CIRCI) arises from dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, altered cortisol metabolism, and tissue resistance to glucocorticoids, all of which can occur during sepsis. Clinical trials of corticosteroids for the treatment of patients with sepsis and septic shock have shown improvements in shock reversal, and in some studies, patient survival; however, their role in the treatment of sepsis in sub-Saharan Africa is unknown. The incidence of sepsis in sub-Saharan Africa is compounded by high rates of human immunodeficiency virus (HIV) and co-infections, including tuberculosis (TB), which is the leading cause of sepsis. Both HIV and TB can cause immune dysregulation and adrenal insufficiency, which may exacerbate CIRCI and prolong shock. Existing sepsis research has been predominantly conducted in high-income countries and has largely excluded people living with HIV or TB. Therefore, there is a need to better understand sepsis and CIRCI pathophysiology in the context of specific regional host and pathogen characteristics. In this narrative review, we explored the pathophysiology of sepsis in sub-Saharan Africa including the existing literature on the immune response to sepsis and the prevalence of adrenal insufficiency in patients with HIV and TB, with a focus on the implications for corticosteroid management. We found a compelling need to further evaluate corticosteroids for the treatment of sepsis in Africa.
Keywords: Sepsis; Pathophysiology; Corticosteroid therapy; Sub-Saharan Africa